Women's Representation in Regional Elections: Gendered Institutions' Perspective on Political Design and Practice - Nasrudin, Rudi; Solihah, Ratnia; Aziz, Yugni Maulana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Women's political representation in local elections (PILKADA) indicates the quality of democracy and the level of gender equality in political institutions. Although gender quotas have increased the number of female candidates, their substantive representation remains low. This study aims to analyze how gendered political institutions influence a qualitative approach based on secondary data research and thematic analysis. Additionally, it examines the elements of gender-focused institutions identified by Joan Acker, which include division of labor, division of power, symbols and discourses, interpersonal relations, and internal mental work. The results prove that structural and cultural challenges still limit women's participation in the electoral political arena. (1) Division of labor, women tend to be pushed into non-strategic campaign roles, strengthening traditional role stereotypes, (2) division of power, women's access to decision-making is limited due to the dominance of male political elites and political dynasties; (3) symbols and discourses, campaign narratives and public representation are still gender-biased, limited to considering women's existence as supporters not leaders; (4) interpersonal relations, informal political networks are masculine and exclusive, marginalizing women from power networks and (5) internal mental work, that social norms and internal expectations create hesitation for women to show themselves as major political actors. Based on these results above, this research can strengthen the understanding that increasing women's representationin quantity is not enough without being accompanied by institutional transformation and political culture. In addition, this study also emphasizes that there needs to be a comprehensive reform of political design and practice to be more inclusive of women's leadership.